Validity And Reliability of The Indonesian Version of Reflux Symptoms Score (RSS) and Reflux Sign Assessment (RSA) - Kandhi, Putu Wijaya (Smart Medical Journal, 2023)
Introduction: Laryngopharyngeal reflux (LPR) symptoms are unspecific and make it difficult for clinicians to make a diagnosis. Several types of questionnaires have been developed to diagnose LPR such as the reflux symptoms score (RSS) and reflux sign assessment (RSA) questionnaires. However, the use of these questionnaires in Indonesia is still experiencing obstacles because there is no Indonesian version that has been tested for validity and reliability. This study aims to evaluate the validity and reliability of the Indonesian versions of RSS and RSA.Methods: This study was an observational analytic study with a cross-sectional design involving 40 patients with LPR during January-March 2023. Questionnaire validity was assessed using external and internal validity methods, while reliability was assessed using internal consistency and test-retest reliability.Results: The Indonesian versions of the RSS and RSA had good internal consistency with Cronbach's α values of 0.734-0.831 and 0.743-0.809 respectively. Test-retest reliability for RSS and RSA was also good with rs of 0.930 and 0.842 respectively with p<0.001 for both questionnaires. The Indonesian versions of RSS and RSA also proved to have good validity with high correlations between RSS with reflux symptoms index (RSI) and RSA with reflux finding score (RFS) with p<0.001 for both questionnaires).Conclusion: The Indonesian versions of the RSS and RSA questionnaires were found to be valid and reliable for the assessment of symptoms and diagnosis of LPR.